ON THE ROLE OF ANATOMICAL AND FUNCTIONAL DISORDERS OF THE FEET IN DEVELOPMENT IDIOPATHIC OSTEOARTHRITIS OF THE KNEE JOINT - Erkinov , N.G.; Asalov , G.S. (Educational Research in Universal Sciences, 2023)
Osteoarthritis (OA) of the knee joint is one of the most common degenerative diseases of the population of Uzbekistan and occupies a leading place among the causes of disability in people over 60 years of age. The rear two forms of knee joint OA: idiopathic and secondary. Idiopathic OA is the case when doctors do not know exactly the causes of the pathological process, which is more than 90%, and secondary – when the cause is known, and OA develops due to injuries or various diseases. As you know, according to the law of dialectics, the reared consequences for no reason. In this case, severe lesions of large joints, when the underlying cause is not established, are called the idiopathic form of OA. This name has become generally accepted among specialists and still no one doubts in term so fits revision. Treatment without taking into account etiological factors does not give the desired stable results, which dictates the need for a deeper study of the pathogenesis of this disease.